2022
DOI: 10.1177/24715492221075460
|View full text |Cite
|
Sign up to set email alerts
|

Remote Follow-up of Shoulder Arthroplasty Patients During COVID-19 Pandemic - Is This the way Forward?

Abstract: Background The COVID-19 Pandemic has affected the way health care systems function across the globe. Apart from eliminating the risk of being in a vulnerable environment during the pandemic such as a hospital setting, virtual arthroplasty follow-up reduces the demand on funding and resources on the National Health Services (NHS). Methods We retrospectively reviewed our shoulder arthroplasty patients (55) operated between October 2018 to November 2020 at both our hospital sites. For remote follow-up, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Mansukhani et al 24 report similar satisfaction with telephone follow-up by a consultant surgeon in their retrospective review. 55 shoulder arthroplasty patients were contacted on a scheduled appointment date ‘to enquire about their wound, pain and function.’ Patients were questioned as per the questionnaire from the Oxford Shoulder Score (OSS) and American Shoulder and Elbow Score (ASES).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Mansukhani et al 24 report similar satisfaction with telephone follow-up by a consultant surgeon in their retrospective review. 55 shoulder arthroplasty patients were contacted on a scheduled appointment date ‘to enquire about their wound, pain and function.’ Patients were questioned as per the questionnaire from the Oxford Shoulder Score (OSS) and American Shoulder and Elbow Score (ASES).…”
Section: Resultsmentioning
confidence: 79%
“…Mansukhani et al 24 report similar satisfaction with telephone follow-up by a consultant surgeon in their retrospective review. 55 shoulder arthroplasty patients were contacted on a scheduled appointment date 'to enquire about their wound, pain and function.'…”
Section: What Format Of Surveillance Can Identify a Failing Implant?mentioning
confidence: 79%
“…These studies found an overall decreased length of postoperative hospital stay, increased discharged-home rate, no significant change in 30-day readmission rates, and an increased use of telemedicine for follow-ups. 1 , 16 ,20,22 The impact of COVID-19 on long-term post-surgical rehabilitation and physical therapy has not been well studied. Evaluating the effect of COVID-19 on long-term postoperative management and rehabilitation of RTSA can provide insight into future management.…”
Section: Introductionmentioning
confidence: 99%